2011
DOI: 10.1021/ja2070957
|View full text |Cite
|
Sign up to set email alerts
|

Green Proteorhodopsin Reconstituted into Nanoscale Phospholipid Bilayers (Nanodiscs) as Photoactive Monomers

Abstract: Over 4,000 putative proteorhodopsins (PRs) have been identified throughout the oceans and seas of the Earth. The first of these eubacterial rhodopsins was discovered in 2000 and has expanded the family of microbial proton pumps to all three domains of life. With photophysical properties similar to those of bacteriorhodopsin, an archaeal proton pump, PRs are also generating interest for their potential use in various photonic applications. We perform here the first reconstitution of the minimal photoactive PR s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
54
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 51 publications
(57 citation statements)
references
References 87 publications
3
54
0
Order By: Relevance
“…3A and B). While it has been reported that oligomerization affects the protein stability and kinetics of the photocycle [41,42], a number of biochemical and biophysical studies have proved that the functional unit of ion-pumping rhodopsins is the monomer [43][44][45], and the physiological role of oligomerizations is still unclear. Further studies are needed to determine why ion pumping rhodopsins form oligomers under physiological conditions.…”
Section: Structure-function Relationships Of Br Hr and Narmentioning
confidence: 99%
“…3A and B). While it has been reported that oligomerization affects the protein stability and kinetics of the photocycle [41,42], a number of biochemical and biophysical studies have proved that the functional unit of ion-pumping rhodopsins is the monomer [43][44][45], and the physiological role of oligomerizations is still unclear. Further studies are needed to determine why ion pumping rhodopsins form oligomers under physiological conditions.…”
Section: Structure-function Relationships Of Br Hr and Narmentioning
confidence: 99%
“…21–26 However, preparing synthetic hosts that contain membrane proteins with native or native-like activities is difficult, given the highly specific conditions required to support the generally complex protein structures 27,28 and dynamics 29,30 that are necessary for protein function. In most cases, membrane proteins can remain functional outside of the native lipid membranes only in the presence of membrane-mimetic surfactants or lipids 3135 and over narrow ranges of solvent compositions and temperatures. 36 Such stability considerations have limited the incorporation of membrane proteins into only a few types of synthetic materials, including hydrogels, 37 block copolymers, 3840 silica gels or glasses, 41,42 self-assembled lipid bilayer arrays, 43,44 and supported lipid bilayers.…”
Section: Introductionmentioning
confidence: 99%
“…In the last decade, the lipid bilayer nanodisc system developed by the Sligar laboratory has become an important tool to characterize membrane proteins (19 -20). Many proteins have been reconstituted in nanodiscs, including human tissue factor (21), bacteriorhodopsin (22)(23), G-protein-coupled receptors (24 -26), chemoreceptor Tar (27)(28), translocon SecYEG (29 -31), and F 0 F 1 -ATPase (32). ABC transporters, such as the maltose system MalEFGK (33-34), the lipid A exporter MsbA (35), and P-glycoprotein (19,36), have also been reconstituted in nanodiscs, albeit generally with a low coupling efficiency.…”
mentioning
confidence: 99%